2022
DOI: 10.3389/fphar.2022.1042189
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and human health: Exploring how the probiotic genus Lactobacillus modulate immune responses

Abstract: The highest density of microbes resides in human gastrointestinal tract, known as “Gut microbiome”. Of note, the members of the genus Lactobacillus that belong to phyla Firmicutes are the most important probiotic bacteria of the gut microbiome. These gut-residing Lactobacillus species not only communicate with each other but also with the gut epithelial lining to balance the gut barrier integrity, mucosal barrier defence and ameliorate the host immune responses. The human body suffers from several inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 126 publications
1
53
0
1
Order By: Relevance
“…This was shown in studies using a range of fermented dairy test foods (fermented milks, kefir, yogurt, and cheese whey protein), providing supporting evidence that fermented dairy foods can positively influence gut microbial characteristics (Kato et al, 2004; Matsumoto et al, 2010; Sprong et al, 2010; Veiga et al, 2010, 2014; Liu et al, 2015; Yilmaz et al, 2019; Li et al, 2020; Zhang et al, 2020). Lactobacillus and Bifidobacterium are considered commensal gut genera, wherein increased relative abundances have been shown to benefit the host (O’Callaghan and van Sinderen, 2016; Hidalgo-Cantabrana et al, 2017; Dempsey and Corr, 2022; Rastogi and Singh, 2022). Thus, increasing the intake of fermented dairy foods may ultimately provide part of a solution in correcting apparent gut microbial dysbiosis in such gastrointestinal disease cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown in studies using a range of fermented dairy test foods (fermented milks, kefir, yogurt, and cheese whey protein), providing supporting evidence that fermented dairy foods can positively influence gut microbial characteristics (Kato et al, 2004; Matsumoto et al, 2010; Sprong et al, 2010; Veiga et al, 2010, 2014; Liu et al, 2015; Yilmaz et al, 2019; Li et al, 2020; Zhang et al, 2020). Lactobacillus and Bifidobacterium are considered commensal gut genera, wherein increased relative abundances have been shown to benefit the host (O’Callaghan and van Sinderen, 2016; Hidalgo-Cantabrana et al, 2017; Dempsey and Corr, 2022; Rastogi and Singh, 2022). Thus, increasing the intake of fermented dairy foods may ultimately provide part of a solution in correcting apparent gut microbial dysbiosis in such gastrointestinal disease cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, great progress was achieved in the study of the mechanisms of symbiosis between lactic acid bacteria and the host. Their main beneficial effects have been shown to include the regulation of the imbalance of the intestinal flora [ 42 ], the strengthening of the intestinal barrier functions [ 23 , 27 , 36 ], the maintenance of homeostasis [ 36 , 43 ], the regulation of the immune system [ 43 ], and the production of neurotransmitters (gut–brain axis) [ 44 ]. It has been also shown that the exopolysaccharide (EPS) produced by lactobacilli has the peculiar ability to modify the microbiota [ 45 ], and to improve the colonization and growth of intestinal bacteria by acting as a carbon source [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Lactobacillus is belonged to phyla Firmicutes, and it is an important constituent of the gut microbiome [4]. These gut-residing Lactobacillus species not only contribute to microflora but also improve the gut barrier integrity [5]. Some strains of Lactobacillus gasseri were proven to be benefit to lipid metabolism [6,7], decreased the Irritable Bowel Syndrome symptom score [8] and changed the composition of intestinal microbiota [9].…”
Section: Introductionmentioning
confidence: 99%